Higher Degree Students (HDR) during COVID-19: Disrupted routines, uncertain futures, and active strategies of resilience and belonging - Gomes, Catherine; Hendry, Natalie Ann; De Souza, Ruth; Hjorth, Larissa; Richardson, Ingrid; Harris, Dan; Coombs, Gretchen (Journal of International Students, 2021)
The wellbeing of higher degree research (HDR) students, or postgraduate students during the COVID-19 pandemic has been of concern. In Australia, international students have queued for food parcels, while headlines report stark drops in international enrolments and the financial bottom line of universities. We undertook a pilot study using ethnographic interview methods to understand the lived experiences of current international and domestic HDR students at an Australian university in Melbourne, from June to August 2020 (n=26). In this paper, we discuss domestic and international students’ experiences during the pandemic. International HDR students faced similar challenges to domestic students, but experienced further stressors as temporary migrants. We discuss their experiences in relation to resilience, understood as a relational and collective quality. We suggest that institutions develop policies and programmes to address resilience and build students’ sense of belonging and connection, informed by how students cope with challenges such as COVID-19.